Plate 14: Glechoma hederacea - Fitton, Sarah Mary; Fitton, Elizabeth (Conversations on Botany, 1817)
Hand-colored lithograph of ground ivy, Glechoma hederacea. Class Didynamia, order Gymnospermia.
Keywords: Ground ivy; Botany; Women botanists; Scientific illustration